Diagnosis and Treatment of Fetal Arrhythmia - Wacker-Gussmann, Annette; Strasburger, Janette F.; Cuneo, Bettina F.; Wakai, Ronald T. (American Journal of Perinatology, 2014)
Aims Detection and careful stratification of fetal heart rate (FHR) is extremely important in all pregnancies. The most lethal cardiac rhythm disturbances occur during apparently normal pregnancies where FHR and rhythm are regular and within normal or low-normal ranges. These hidden depolarization and repolarization abnormalities, associated with genetic ion channelopathies cannot be detected by echocardiography, and may be responsible for up to 10% of unexplained fetal demise, prompting a need for newer and better fetal diagnostic techniques. Other manifest fetal arrhythmias such as premature beats, tachycardia, and bradycardia are commonly recognized.Methods Heart rhythm diagnosis in obstetrical practice is usually made by M-mode and pulsed Doppler fetal echocardiography, but not all fetal cardiac time intervals are captured by echocardiographic methods.Results and Conclusions This article reviews different types of fetal arrhythmias, their presentation and treatment strategies, and gives an overview of the present and future diagnostic techniques.
Keywords: fetal arrhythmia; magnetocardiography; electrocardiography; tachycardia; bradycardia; stillbirth; long QT syndrome; fetal demise